Strategi Komunikasi Efektif Berbasis Al-Qur'an dan Hadits untuk Meningkatkan Kinerja Lembaga Pendidikan Islam - Imam Fauji; Eko Budi Supriyanto (Laskar Karya, 2025)
This study aims to identify and analyze educational strategies based on the values of the Qur'an and Hadith in efforts to improve the performance of Islamic educational institutions. Using the Systematic Literature Review (SLR) method, this research examines various relevant sources related to Islamic educational principles, including honesty, justice, empathy, openness, and constructive advice. The results of the study indicate that the implementation of educational values derived from the Qur'an and Hadith plays a significant role in fostering harmonious relationships within the institution, enhancing the motivation of educators, and creating a work culture aligned with Islamic values. Moreover, the application of education strategies based on Qur'anic and Hadith values contributes to improving the reputation of Islamic educational institutions in the eyes of the community, thereby strengthening public trust. This study offers several practical recommendations to enhance the effectiveness of educational strategies in Islamic institutions, including training programs on Islamic educational values for teachers, performance evaluations based on consultation and advice principles, and encouraging active participation of all stakeholders in decision-making processes. It is expected that these strategies will help Islamic educational institutions optimize their performance and foster an educational environment that is integral, harmonious, and of high quality